Jasmonates Alleviate the Harm of High-Temperature Stress During Anthesis to Stigma Vitality of Photothermosensitive Genetic Male Sterile Rice Lines - Chen, Jing; Miao, Wenqian; Fei, Keqi; Shen, Hongli; Zhou, Yujiao; Shen, Yan; Li, Chaoqing; He, Jiang; Zhu, Kuanyu; Wang, Zhiqin; Yang, Jianchang (Frontiers in Plant Science, 2021)
Using photo-thermo-sensitive genic male sterile (PTSGMS) rice (Oryza sativa L.) lines to produce hybrids can obtain great heterosis. However, PTSGMS rice lines exhibit low stigma vitality when high temperature (HT) stress happens during anthesis. Jasmonates (JAs) are novel phytohormones and play vital roles in mediating biotic and abiotic stresses. Little is known, however, if and how JAs could alleviate the harm of HT stress during anthesis to the stigma vitality of PTSGMS lines. This study investigated the question. Two PTSGMS lines and one restorer line of rice were pot-grown and subjected to normal temperature and HT stress during anthesis. The stigma exertion rate, sigma fresh weight, stigma area, contents of JAs, hydrogen peroxide (H2O2), and ascorbic acid (AsA), activity of catalase in stigmas, and the number of pollens germinated on the stigma of PTSGMS lines were determined. The results showed that a rice line with higher JAs content in the stigma under HT stress showed lower H2O2 content, higher AsA content and catalase activity in stigmas, larger stigma area, heavier stigma fresh weight, more number of pollens germinated on the stigma, and higher fertilization and seed-setting and rates. Applying methyl jasmonate during anthesis to rice panicles decreased the accumulation of reactive oxygen species and enhanced stigma vitality, thereby increasing fertilization and seed-setting rates of the hybrids of PTSGMS rice lines under HT stress. The results demonstrate that JAs attenuate the injury of HT stress to the stigma vitality of PTSGMS rice lines through enhancing antioxidant ability.